A functional variant of ATG16L2 is associated with Crohn's disease in the Chinese population. (3rd November 2016) - Ma, T.; Wu, S.; Yan, W.; Xie, R.; Zhou, C.
Abstract: Aim: To determine whether genetic polymorphism of the ATG16L2 gene is functionally associated with the incidence of Crohn's disease (CD) in the Chinese population. Method: The single nucleotide polymorphism (SNP) rs11235604 of the ATG16L2 gene was genotyped in 363 patients with CD and 486 healthy volunteers from the Chinese Han population. The distributions of the genotype and allele frequency were compared between patients and controls by the chi‐square test. The mRNA expression of ATG16L2 in T cells was evaluated by real‐time PCR. Comparisons of mRNA expression of ATG16L2 between patients and controls and between patients with genotype CC and genotype CT/TT were performed with the Student's t ‐test. Results: Compared with the controls, patients were found to have a significantly higher proportion of genotype TT (5.5% vs 2.5%, P  =   0.04). Allele T was the risk allele for the disease (16.3% vs 12.3%, P  =   0.02), with an odds ratio of 1.31 (95% CI 1.04–1.67). The ATG16L2 mRNA of the patients was significantly reduced when compared with the controls (0.0044 ± 0.0018 vs 0.0064 ± 0.0023, P  <   0.001). Patients with genotype TT/CT had a significant lower level of ATG16L2 mRNA than patients with genotype CC (0.0036 ± 0.0016 vs 0.0053 ± 0.0028, P  =   0.005). Conclusions: ATG16L2 is a susceptibility gene for CD in the Chinese population. The rs11235604 SNP is remarkably associated with downregulation of the expression of ATG16L2 . Further investigation into the gene's function is warranted for a comprehensive knowledge of the contribution of the variant to the development of CD.